2022
DOI: 10.1021/acsphyschemau.2c00020
|View full text |Cite
|
Sign up to set email alerts
|

Toward Computing Accurate Free Energies in Heterogeneous Catalysis: a Case Study for Adsorbed Isobutene in H-ZSM-5

Abstract: Herein, we propose a novel computational protocol that enables calculating free energies with improved accuracy by combining the best available techniques for enthalpy and entropy calculation. While the entropy is described by enhanced sampling molecular dynamics techniques, the energy is calculated using ab initio methods. We apply the method to assess the stability of isobutene adsorption intermediates in the zeolite H-SSZ-13, a prototypical problem that is computationally extremely challenging in terms of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 65 publications
0
30
0
Order By: Relevance
“…It uses DFT-D as a low-level method for the full periodic structure and second-order Møller–Plesset perturbation theory (MP2) as a high-level method for cluster models to locally describe the molecule–surface interactions. This hybrid MP2:DFT-D approach has been shown to yield MP2 quality adsorption energies for the whole periodic structure. ,, While it reduces the computational effort by 3 orders of magnitude compared to periodic MP2, it is still 2 orders of magnitude more expensive than DFT-D and only affordable for a few selected structures, e.g., the most stable adsorption complexes, but not for sampling the entire PES beyond these minimum-energy structures. Instead of the harmonic approximation around a minimum-energy structure (local approach, sometimes called “static”) , molecular dynamics (MD) is used for the global sampling of the PES. ,,,, This is essential to capture global anharmonicity and to properly describe the temperature-dependent spatial distribution of adsorbed molecules. However, MD simulations require easily 100,000 or more energy and force calculations to provide converged adsorption energies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It uses DFT-D as a low-level method for the full periodic structure and second-order Møller–Plesset perturbation theory (MP2) as a high-level method for cluster models to locally describe the molecule–surface interactions. This hybrid MP2:DFT-D approach has been shown to yield MP2 quality adsorption energies for the whole periodic structure. ,, While it reduces the computational effort by 3 orders of magnitude compared to periodic MP2, it is still 2 orders of magnitude more expensive than DFT-D and only affordable for a few selected structures, e.g., the most stable adsorption complexes, but not for sampling the entire PES beyond these minimum-energy structures. Instead of the harmonic approximation around a minimum-energy structure (local approach, sometimes called “static”) , molecular dynamics (MD) is used for the global sampling of the PES. ,,,, This is essential to capture global anharmonicity and to properly describe the temperature-dependent spatial distribution of adsorbed molecules. However, MD simulations require easily 100,000 or more energy and force calculations to provide converged adsorption energies.…”
Section: Methodsmentioning
confidence: 99%
“…Instead of the harmonic approximation around a minimum-energy structure (local approach, sometimes called “static”) , molecular dynamics (MD) is used for the global sampling of the PES. ,,,, This is essential to capture global anharmonicity and to properly describe the temperature-dependent spatial distribution of adsorbed molecules. However, MD simulations require easily 100,000 or more energy and force calculations to provide converged adsorption energies.…”
Section: Methodsmentioning
confidence: 99%
“…A few very recent achievements have been reported that open the door to more systematic investigation of this question in the near future. 302 At the GGA+dispersion level of theory currently accessible for AIMD of hydrocarbons in zeolites, secondary carbenium ions are not always deep free energy minima and easily lead to spontaneous transfer of the proton to the zeolite framework, yielding the corresponding π-complex. 306,309,310 Notably, most investigations cited so far deal with the stability of carbenium ions in the bulk structure of zeolites, in the vicinity of bridging Si−(OH)−Al groups.…”
Section: Stability Of Carbocations In Zeolitesmentioning
confidence: 99%
“…In ref 361, alkoxides are invoked as intermediates in that respect, but computational results tend to show that neutral π-complexes are expected to play a dominant kinetic role with respect to alkoxides. 302,306,310,363 For cyclic alkenes (in the case of an endocyclic C�C bond), three kinds of skeletal isomerization reactions can take place. 6 Type A isomerization is split in two subcategories (Figure 12c,d).…”
Section: Skeletal Isomerizationmentioning
confidence: 99%
See 1 more Smart Citation